OPTIMIZING ACCOUNTING GRADUATE COMPETENCIES FROM THE PERSPECTIVE OF STUDENTS, LECTURERS, AND GRADUATE USERS IN THE DIGITALIZATION 5.0 ERA - Irne Aryanie; Ella Rahmayanti; Murni; Mardiaton; Munawarah (RADJA PUBLIKA, 2026)
This study aims to examine differences in perceptions between students, lecturers, and graduate users regarding 21 competency attributes of accounting graduates. Respondents in this study were students and lecturers from 4 state universities and 4 private universities, as well as graduate users from 7 types of industries. The total sample in this study was 120 samples, and hypotheses were tested using One-Way ANOVA analysis. The results of this study showed no significant differences between the sample groups. Meanwhile, the most important competency attributes were honesty, work ethic, willingness to continue learning, and the ability to operate accounting software, as well as responsibility.